Immediate changes in transcription factors and synaptic transmission in the cochlea following acoustic trauma: A gene transcriptome study. (April 2021) - Maeda, Yukihide; Kariya, Shin; Uraguchi, Kensuke; Takahara, Junko; Fujimoto, Shohei; Sugaya, Akiko; Nishizaki, Kazunori
Highlights: Cochlear pathologic mechanisms immediately after onset of noise trauma remain unclear. Transcription factors (25 genes) are regulated in mice cochleae after noise trauma. Neurotransmitter receptors (28 genes) are regulated in cochleae after noise trauma. A transcription factor, Atf3 is upregulated in the organ of Corti after noise trauma. The data of cochlear gene transcriptome may help developing therapy for hearing loss. Abstract: Pathologic mechanisms in cochleae immediately following the onset of noise-induced hearing loss (NIHL) remain unclear. In this study, mice were exposed to 120 dB of octave band noise for 2 h to induce NIHL. Three hours after noise exposure, expression levels of the whole mouse genome in cochleae were analyzed by RNA-seq and DNA microarray. Differentially expressed genes (DEGs) exhibiting >2-fold upregulation or downregulation in noise-exposed cochleae compared to controls without noise exposure were identified. RNA-seq and microarray analyses identified 273 DEGs regulated at 3 h post-noise (51 upregulated and 222 downregulated). Bioinformatic analysis revealed that these DEGs were associated with the functional gene pathway "neuroactive ligand-receptor interaction" and included 28 genes encoding receptors for neurotransmitters such as gamma-aminobutyric acid and glutamate. Other DEGs included 25 genes encoding transcription factors. Downregulation of 4 neurotransmitter receptors ( Gabra3, Gabra5, Gabrb1, Grm1 ) and upregulations of 5 transcription factors ( Atf3, Dbp, Helt, Maff, Nr1d1 ) were validated by RT-PCR. The differentially regulated transcription factor Atf3 immunolocalized to supporting cells and hair cells in the organ of Corti at 12-h post-noise. The present data serve as a basis for further studies aimed at developing medical treatments for acute sensorineural hearing loss.